Scheduling and Control of a Wafer Transfer Robot for Foundry Equipment Innovation Competition. Issue 15 (2019) - Song, Kai-Tai; Ou, Song-Qing; Yang, Cheng-An; Sun, Yu-Xuan; Kang, Li-Ren; Wang, Zhen-Yu; Wang, Yu-Shin; Lu, Pei-Chun; Ko, Chun-Long; Chen, Yao Hsiang
Abstract: This paper presents a design and implementation of a wafer transfer robotic system for a Foundry Equipment Innovation Competition. In this system, a 4-DOF robotic arm was designed and constructed for wafer transfer between a cassette and processing chambers. The purpose of this competition was to promote intelligent automation for wafer fabrication, in which multiple wafers and chambers need to be handled simultaneously. A scheduling algorithm is proposed for efficient task execution of wafer to process recipes assigned during the competition. The task also features to integrate defect detection and endpoint determination of wafer processing. The robot was required to receive the processing data from the mission platform to determine the endpoint of wafer processing in a chamber and complete the recipe automatically. The online inspection algorithm detects wafer defects during the task execution and report to the task planner. The state of each wafer and chamber are taken into consideration for scheduling in order to complete the wafer fabrication in an efficient and flexible manner. The developed robotic system spent 9 minutes to complete the assigned mission of transferring 6 wafers among multiple chambers and 2 cassettes and achieved 93.4% defect-detection rate in the competition.